1997
DOI: 10.1088/0953-8984/9/6/003
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between open volume defects and deposition conditions of superconducting thin-film

Abstract: The relationship between the open volume defects and the deposition conditions of superconducting thin-film was studied by the position lifetime technique. Using a low-energy pulsed positron system, positron lifetime as a function of implantation energy was measured on epitaxial superconducting thin-film deposited on yttrium stabilized cubic zirconia substrates (YSZ) with pulsed laser deposition in a partial pressure of air under different conditions. The results show that the type of open volume defect is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similar studies, performed using the same instrument, followed on YBa 2 CuO 7-δ thin films deposited by PLD on YSZ crystal substrates [84], and on YBa 2 CuO 7-δ thin films deposited by coevaporation on LaAlO 3 crystal substrates [85]. The PLD grown films were nominally 400 nm thick and the variation in the mean positron lifetime, τ ave , with implantation energy showed a plateau in the range 3-8 keV where the positrons were implanting into the bulk of the thin film.…”
Section: Ve-pas Of Perovskite-related Oxide Superconductor Thin Filmsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar studies, performed using the same instrument, followed on YBa 2 CuO 7-δ thin films deposited by PLD on YSZ crystal substrates [84], and on YBa 2 CuO 7-δ thin films deposited by coevaporation on LaAlO 3 crystal substrates [85]. The PLD grown films were nominally 400 nm thick and the variation in the mean positron lifetime, τ ave , with implantation energy showed a plateau in the range 3-8 keV where the positrons were implanting into the bulk of the thin film.…”
Section: Ve-pas Of Perovskite-related Oxide Superconductor Thin Filmsmentioning
confidence: 94%
“…Near-Surface Depth Profiling of Solids by Mono-Energetic Positrons component from the 5 keV spectra were presented for various films studied. The second lifetime value was constant at ~326 ps and had an intensity that varied from ~17 % to ~47 % and was not assigned to a specific type open volume defect [84]. There was no correlation between the superconducting transition temperature of the film and the intensity of the vacancy-related defect component.…”
mentioning
confidence: 89%
“…The lower value of S in the film deposited at 60 mTorr can be attributed to the lower defect concentration that resulted from the competition between the two functions of the deposition oxygen pressures. Previously, Zhou et al [18] reported that the concentration of the defects increases with increase in air partial pressures on an epitaxial YBa 2 Cu 3 O 7−x film. Here, we observed that the concentration of the defects increases both with the increase in oxygen pressure and with the reduction in oxygen.…”
Section: Variation Of the S Parameter With Deposition Oxygen Pressurementioning
confidence: 99%